2007
DOI: 10.1007/s00267-006-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

Early Vegetation Development on an Exposed Reservoir: Implications for Dam Removal

Abstract: The 4-year drawdown of Horsetooth Reservoir, Colorado, for dam maintenance, provides a case study analog of vegetation response on sediment that might be exposed from removal of a tall dam. Early vegetation recovery on the exposed reservoir bottom was a combination of (1) vegetation colonization on bare, moist substrates typical of riparian zones and reservoir sediment of shallow dams and (2) a shift in moisture status from mesic to the xeric conditions associated with the pre-impoundment upland position of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
5
19
0
1
Order By: Relevance
“…However, consistent with Orr and Stanley () and Auble et al . (), we found no clear evidence (Figure ) of nonnative species richness and abundance increasing with time since removal.…”
Section: Evaluating the Cmcsmentioning
confidence: 99%
“…However, consistent with Orr and Stanley () and Auble et al . (), we found no clear evidence (Figure ) of nonnative species richness and abundance increasing with time since removal.…”
Section: Evaluating the Cmcsmentioning
confidence: 99%
“…(), Orr and Stanley (), and Auble et al. (), who observed rapid and dense revegetation after dam removal. Cross‐tabulation maps revealed that colonization peaked between March and May, when the colonized area increased from 30% to 65% (Figures and ) as soon as weather conditions were suitable.…”
Section: Discussionmentioning
confidence: 96%
“…Restoration project managers need to monitor the effectiveness of recolonization to avoid erosion of non-vegetated sediments. The few studies focusing on colonization after dam removal showed that initial colonization is characterized by its pioneer vegetation (mostly herbaceous) and short duration of this period of initial colonization (usually one or two years (Shafroth et al, 2002;Gurnell, Boitsidis, Thompson, & Clifford, 2006;Orr & Stanley, 2006;Auble, Shafroth, Scott, & Roelle, 2007;Stephens, 2017). These results highlight that managers have a short window of opportunity for action.…”
Section: Introductionmentioning
confidence: 99%
“…The role of hydrology in shaping riparian vegetation is well established: rates of stage change influence seedling germination and recruitment (Mahoney and Rood, 1998); species present at a site reflect inundation period (Auble et al, 2005); change in moisture status correlates with change in species composition over a time span of several years (Auble et al, 2007); plant communities differ by elevation with respect to the floodplain (Chapin et al, 2002); vegetation type varies in relation to flow frequencies that determine sediment mobilization and effective discharge (Pike and Scatena, 2010). This study adds to this knowledge by demonstrating correlations between flood stages of different recurrence intervals and mean stage of the riparian edge for various process domains.…”
Section: Hydrologic Relationshipsmentioning
confidence: 99%